Deconstructing Elon Musk's Rhetorical Prowess: A Pragmatic Analysis of Speech Acts in His TED Talk - Bahrani, Bahrani; Irawati, Dini; Hadijah, Sitti; Erangga, Suwarid (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2024)
This research comprehensively analyzes Elon Musk's speech acts during his TED Talk Show episode "Tesla, Twitter and How His Brain Works", employing an integrated speech act theory approach. The identified locutionary, illocutionary, and perlocutionary acts reveal Musk's strategic tactics for maintaining engagement, shaping perceptions, and influencing decision-making. A qualitative approach with a pragmatics perspective analyzed Musk's speech acts in the Talk Show, using a transcription from YouTube as data source for his utterances. The findings showed Musk's locutionary acts aligned with facework and politeness theories, fostering self-presentation. His illocutionary acts like assertions, accusations, questioning, promises, and commands resonated with persuasive discourse applications of speech act theory. Perlocutionary effects causing concern, amusement, persuasion, inspiration, and curiosity generation reflected perlocutionary act concepts influencing audience perceptions. Integrating these frameworks offers insights into Musk's multifaceted strategies, highlighting speech act components' interplay in achieving outcomes. The findings contribute understandings of effective leadership communication and persuasion. While acknowledging limitations, the research holds pedagogical implications for enhancing English learners' public speaking, persuasive discourse, and cross-cultural communication skills by integrating theory and applications.